Altered Cytokine Expression and Barrier Properties after In Vitro Infection of Porcine Epithelial Cells with Enterotoxigenic Escherichia coli and Probiotic Enterococcus faecium - Martina Kern; Dorothee Günzel; Jörg R. Aschenbach; Karsten Tedin; Angelika Bondzio; Ulrike Lodemann (Hindawi Limited, 2017)
The aim of the present study was to elucidate the effects of the probiotic feed additive Enterococcus faecium NCIMB 10415 (E. faecium) on porcine jejunal epithelial cells (IPEC-J2) during an in vitro challenge with enterotoxigenic Escherichia coli (ETEC). Cells were incubated with E. faecium, ETEC, or both, and the effects on barrier function and structure and intra- and intercellular signaling were determined. Coincubation with E. faecium abolished the ETEC-induced decrease in transepithelial resistance (Rt) (p≤0.05). No differences were seen in the expression levels of the intercellular connecting tight junction proteins examined. However, for the first time, a reorganization of the monolayer was observed in ETEC-infected cells but not in coincubated cells. ETEC induced an increase in cytotoxicity that was prevented by coincubation (p≤0.05), whereas apoptosis rates were not affected by bacterial treatment. ETEC increased the mRNA expression and release of proinflammatory cytokines TNF-α, IL-1α, and IL-6 which could be prevented by coincubation for TNF-α mRNA expression and IL-6 protein (p≤0.05). Likewise, cAMP concentrations elevated by ETEC were reduced in coincubated cells (p≤0.05). These findings indicate a protective effect of the probiotic E. faecium on inflammatory responses during infection with ETEC.